2019
DOI: 10.1016/j.ijid.2019.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Two types of poor immunological responder showing distinct responses to long-term HAART

Abstract: Most previous studies on poor immunological responders (PIRs) have been performed on one cohort at one time-point following highly active antiretroviral therapy (HAART). The aim of this study was to investigate whether there are different subtypes of PIR and whether a certain population might achieve better immune reconstitution following longer HAART. Methods: This study was designed as an ambispective cohort study, including a 4-5-year retrospective study and a 2-year prospective follow-up investigation. Thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…These PIRs had a higher risk of AIDS-related and non-AIDS complications, such as cardiovascular disease, bone, and renal disease, neurocognitive decline, and premature aging ( 40 43 ). Notably, PIRs had higher rates of morbidity and mortality than IRs ( 5 ). Thus, there is an urgent need to identify PIRs early and provide effective treatment as soon as possible.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These PIRs had a higher risk of AIDS-related and non-AIDS complications, such as cardiovascular disease, bone, and renal disease, neurocognitive decline, and premature aging ( 40 43 ). Notably, PIRs had higher rates of morbidity and mortality than IRs ( 5 ). Thus, there is an urgent need to identify PIRs early and provide effective treatment as soon as possible.…”
Section: Discussionmentioning
confidence: 98%
“…The expression of ectonucleotidases (CD39 and CD73) on αβDNT and activated Treg cells was evaluated by flow cytometry. The gating strategy for activated Treg cells was performed as previously described ( 5 ). PBMCs were stained with directly conjugated antibodies for 30 min at 4°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 However, our previous study indicated that thymic output and CD4 + T-cell recovery could be further improved after long-term ART. 46 Thus, a longer follow-up may be required after the ART to assess CD4 + T-cell function status. In addition, our results highlight the importance of developing novel, effective HIV treatments that can overcome the limitations of ART.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + cell count > 350 cells/µL and HIV RNA < 200 copies/mL after cART are considered as a successful treatment in PLWHs [ 20 ]. The humoral and cellular immune responses to HBV vaccination in these satisfactory patients when they are vaccinated with 20 µg of recombinant HBV DNA vaccine at weeks 0, 4, and 24 are unknown at present.…”
Section: Introductionmentioning
confidence: 99%